Implementation of flow control over WirelessHART sensor network using WirelessHART adaptors - Sabo Miya Hassan; Kishore Bingi; Rosdiazli Ibrahim; Lim Jin Chein; ThasarathaRao Supramaniam (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Despite the advantages of the industrial wireless standards such as WirelessHART, ISA100.11a and Wireless Networks for Industrial Automation-Process Automation (WIA-PA), their application still faces a lot of challenges especially when it comes to interfacing with the real plant. This is due to lack of adequate infrastructures such as interfacing circuitry to establish communication between the WirelessHART nodes and the actuators and sensors. Therefore, this paper presents the application of locally developed WirelessHART adaptors for flow process control. The adaptors serve as an interface between the WirelessHART network and the sensor and actuator of the plant. Experimental results of the controllers compared showed that wireless control is possible through the use of the adaptors.